Erotika pathemata nel teatro eschileo: un itinerario - Francesco Carpanelli (Annali Online dell'Università di Ferrara. Sezione Lettere)
Fragments of Aeschylus need a careful review by scholars, especially after the latest collections recently produced. This paper attempts to bring together some fragmentary works of the author under the common theme of Love in such a way as to provide an example of how it should work in connection with the texts as we have, in this case The Suppliants. Poetic texts after the fifth century BC., both Greek and Latin, and archaeological production, may give new life to the myths dealt by the tragedians that would otherwise be lost if they were committed only to the reading of a few surviving fragments.